Zinc oxide reinforced poly(para-aminophenol) nanocomposites: Structural, thermal stability, conductivity and ammonia gas sensing applications. Issue 10 (27th September 2022) - Furhan,; Ramesan, M. T.
Abstract: Conducting polymer nanocomposites based on poly( para -aminophenol) (PpAP) with various concentrations of zinc oxide (ZnO) nanoparticles were synthesized by in-situ polymerization and their structural, morphological, thermal and electrical properties were evaluated. X-ray diffraction and Fourier transform infrared analysis were used to ascertain the interfacial interactions between ZnO and PpAP. The scanning and transmission electron microscopic images demonstrate the variation in morphology of composites with a homogenous growth of spherically shaped nanoparticles in the polymer matrix. Thermogravimetric studies supported the increased thermal stability of the composites compared to the parent polymer, and thermal activation energy from the Coats-Redfern method further corroborated this finding. The dielectric properties and AC conductivity increase with the addition of nanoparticles up to 7 wt.% and beyond that, these properties decrease. The applicability of various theoretical models for predicting the dielectric constant for PpAP/ZnO nanocomposites was evaluated. The synthesized nanocomposites were used for detecting ammonia gas at room temperature, and the composite with 7 wt.% sample had the best gas sensing performance. Finally, the gas-sensing mechanism has been systematically studied to illustrate the improved sensing properties combining p-n junction with interfacial interactions. The excellent properties of these nanocomposites provide a new horizon for designing gas-sensors and nano-electronic devices. Graphical Abstract: UF0001